Thermal Stability of Phage Peptide Probes Vs. Aptamer for Salmonella Detection on Magnetoelastic Biosensors Platform. (16th August 2016) - Chen, I-Hsuan; Horikawa, Shin; Du, Songtao; Liu, Yuzhe; Wikle, Howard Clyde; Barbaree, James M; Chin, Bryan A
Abstract : Rapid and reliable detections for foodborne pathogens are essential to monitor food and improve food safety procedures. Food monitoring, such as monitoring contaminated foods in poultry processing plants and/or field farms with high heat environments, requires thermostable bio-probes on the sensor surfaces for accurate detections. Phage based magnetoelastic (ME) biosensors have been recently developed as a real-time and wireless platform for Salmonella enterica serotype Typhimurum detection in various food systems. The thermostability of phage and aptamer probes were studied here and their binding to Salmonella Typhimurium cells were evaluated using enzyme-linked immunosorbent assay (ELISA) format at various temperatures. The ELISA format can be used to mimic the probe immobilization conditions on ME sensor surfaces and can test bio-probes' performance without the variability that arises from different ME sensor lots. The results of this study can be further applied in the development of the ME biosensor platform.